Successful Aging, Social Isolation, and COVID-19: Do Restrictions Help or Hinder? - Marks, Ray (Journal of Aging Research And Healthcare, 2021)
Background Aging, a commonly accepted time period of declining heath has been shown to vary in terms of its impact on function and independence. Aims This mini review examines the current impact of COVID-19 on the goal of ‘successful aging’, a conceptual model and outcome variable deemed desirable, but hard to attain. Methods Peer reviewed articles published between March 1 2020 and April 15 2021 focusing on ‘successful aging’ and COVID-19 secondary impacts, as located in the PUBMED data base were specifically sought. Results Despite a lack of consensus on the concept of ‘successful aging, and whether this can be achieved or not, ample evidence points to a severe secondary impact on efforts to age as successfully as possible by older adults, especially those isolated in the community as a result of lockdowns. Conclusion Pursuing more efforts to counter predictable harmful cognitive as well as physical impacts of lockdowns, resource and movement restrictions is urgently needed.
Keywords: Aging; COVID-19; Home-Isolation; Older Adults; Social Isolation; Successful aging